Hybridity and Soft Power Statecraft: The 'GREAT' Campaign. Issue 1 (2nd January 2020) - Surowiec, Paweł; Long, Philip
ABSTRACT: This examination analyses transformations to statecraft accelerated by digital media technologies. This theory-building study moves beyond digitalisation of diplomacy as a means of adapting statecraft to evolving media landscapes, and extends to the governance of soft power capabilities. It challenges static approaches to digital diplomacy and argues for conceptualisations of soft power that account for changes to statecraft. To theorise this dynamic, the concept of 'soft power statecraft' and the notion of hybridity in the analysis of 'GREAT', Britain's prominent strategic campaign, reveal trajectories of change elicited by it. The findings, drawn from interviews, policy data, and media artefacts, reveal how 'GREAT' embodies a hybridised approach to soft power statecraft at the levels of governance, communicative practices, media landscapes, and cultures. They reveal how these changes translate into statecraft strategies for the articulation of soft power.